2009
DOI: 10.2298/hel0951161k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of broomrape resistance in sunflower hybrids

Abstract: Broomrape (Orobanche cernua Loeffl.) is the most serious problem in sunflower production in Turkey, some East European countries and Spain. A research covering broomrape tests of sunflower hybrids in the trials based on National Sunflower Research Project was conducted in Trakya region, which holds 75% of the sunflower production in Turkey, in 2006, 2007 and 2008. Based on this project, in conditions of natural infestation, 306, 443 and 533 commercial and candidate hybrids, inbred lines, etc. were tested in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
(6 reference statements)
2
8
0
Order By: Relevance
“…IMIH cultivars were second with 40.88%, followed by NRH cultivars with 9.65% (Table 8). These results support those of Kaya et al, (2009) indicating that over 90% of the sunflower areas in the Thrace region were infested with new broom- rape races and that broomrape and weed control were the main factors in sunflower production.…”
Section: Adoption Ratesupporting
confidence: 88%
“…IMIH cultivars were second with 40.88%, followed by NRH cultivars with 9.65% (Table 8). These results support those of Kaya et al, (2009) indicating that over 90% of the sunflower areas in the Thrace region were infested with new broom- rape races and that broomrape and weed control were the main factors in sunflower production.…”
Section: Adoption Ratesupporting
confidence: 88%
“…Sunflower oil export and import values of Turkey (Anonymous, 2017c Table 6. Sunflower seed processing capacity and sunflower oil consumption in Turkey (Anonymous, 2017c (Tan, 1993;Kaya et al, 2004;Kaya and Evci, 2007;Kaya et al, 2009;Kaya, 2010;Tan, 2010a, b, c;Kaya et al, 2013Kaya et al, , 2014Kaya, 2016). In Turkey, the main constraints for sunflower are attacks by broomrape and downy mildew (DM) but resistance is available to both parasites.…”
Section: Sunflower Research In Turkeymentioning
confidence: 99%
“…In Turkey, the main constraints for sunflower are attacks by broomrape and downy mildew (DM) but resistance is available to both parasites. Sunflower rust races have been identified under field conditions (Kaya et al, 2004;Kaya and Evci, 2007;Kaya et al, 2009;Tan, 2010a, b, c;b;Kaya et al, 2012Kaya et al, , 2013Kaya et al, , 2014Tan, 2014;Tan et al, 2016a, b;Tan et al, 2017a, b).…”
Section: Sunflower Research In Turkeymentioning
confidence: 99%
“…Initially, all of them were named as race F though the relationship between the different F races has not been studied. Nowadays, populations overcoming resistance sources to race F, named as races G and H, have been identified in most of these countries (Kaya et al, 2009; Pacureanu-Joita et al, 2009; Shindrova and Penchev, 2012; Antonova et al, 2013; Martín-Sanz et al, 2016). As mentioned for race F, no comparative studies have been conducted between races G and H reported in different countries.…”
Section: Introductionmentioning
confidence: 99%